Public Hospital Type C Pekan Labuhan - Nelson M. Siahaan; Audina Muhvira (International Journal of Architecture and Urbanism, 2017)
The rapid economic growth in Medan Labuhandistrict has an impact on improving living standards and population growth. This is also in line with the availability of public facilities and infrastructure because the higher the level of one's life, the higher the quality of facilities. Furthermore it is needed a container to full fill the need for medical services both medical and non medical are realized through the design of "Public Hospital Type C Pekan Labuhan" with the aim as a container that provides health services and conduct activities related to health and supported by the facilities within it to achieve that goal. Public Hospital Type C Pekan Labuhan is designedbyapplying neo vernacular architectural themes so that it canalign this building in surrounding buildings and able tosupport the existence of heritage conservation areaactivities in this region. Public Hospital PekanLabuhan asone of the hospitals certified Class C Hospital is expectedto function by the Regulation of the Minister of Health of the Republic of Indonesia.